Knockdown of RIPK2 Inhibits Proliferation and Migration, and Induces Apoptosis via the NF-κB Signaling Pathway in Gastric Cancer - Yang, Qian; Tian, Shan; Liu, Zhengru; Dong, Weiguo (Frontiers in Genetics, 2021)
RIPK2 is a 62 kDa protein and a member of the receptor interacting protein kinases (RIPK) family. It was previously demonstrated that RIPK2 might play a role in promoting malignant tumor progression; however, the precise function of RIPK2 in the onset and progression of gastric cancer (GC) remains unclear. In the current study, we investigated the role of RIPK2 in GC. First, we explored the expression levels of RIPK2 in multiple cancers, including GC, using a bioinformatics approach. We constructed the RIPK2-associated protein-protein interaction network using the search tool for the retrieval of interacting genes/proteins for gene ontology and Kyoto encyclopedia of genes and genomes analysis. Next, we compared the RIPK2 expression levels between GC cells and normal gastric mucosal epithelial cell (GES-1) using reverse transcription quantitative PCR analysis. We downregulated the expression of RIPK2 in GC cells to determine the effects of RIPK2 on cell growth, migration, and apoptosis. Finally, we used western blotting to investigate the RIPK2 downstream signaling pathway involved in the regulation of GC progression. Our results showed that RIPK2 was overexpressed in various tumor tissues, including GC, compared to non-cancer tissues. Moreover, RIPK2 expression was significantly upregulated in all four GC cell lines (MGC-803,SGC-7901, HGC-27 and AGS) comparing the GES-1 cells. Silencing of RIPK2 suppressed GC cell growth by inhibiting migration, and inducing apoptosis through the nuclear factor-κB (NF-κB) signaling pathway. In summary, we demonstrate that RIPK2 plays an important role in modulating GC cell proliferation, migration, and apoptosis through the NF-κB signaling pathway. Therefore, RIPK2 functions as a potential oncogene. We believe that RIPK2 can be used as a candidate biomarker, as well as a diagnostic tool, and the therapeutic target for GC.